2018
DOI: 10.1111/jpn.12861
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of experimental hyperthyroidism on declined immunity of broiler chicken

Abstract: Thyroid hormones (THs) are involved in the development of lymphoid organs and regulation of immune function in birds. However, their role as an immune-modulator in the hyperthyroid state is still debatable. To explore the interrelationship of thyroxine (T ) and the immune system, chicks were divided into three groups. Group I was comprised of control birds, who received the basal diet while group II and III were given diets supplemented with 5 μg and 10 μg thyroxine/kg feed, respectively, from 15 to 28 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Dogs with GBM have a high incidence of concurrent hyperadrenocorticism, hypothyroidism, and hyperlipidemia . These metabolic disturbances cause immune dysregulation in various species and may contribute to the development of, or magnify, cholecystitis (infectious and sterile) in dogs with GBM . Alternatively, it has been suggested that GBMs in dogs may be a consequence of primary chronic cholecystitis .…”
Section: Discussionmentioning
confidence: 99%
“…Dogs with GBM have a high incidence of concurrent hyperadrenocorticism, hypothyroidism, and hyperlipidemia . These metabolic disturbances cause immune dysregulation in various species and may contribute to the development of, or magnify, cholecystitis (infectious and sterile) in dogs with GBM . Alternatively, it has been suggested that GBMs in dogs may be a consequence of primary chronic cholecystitis .…”
Section: Discussionmentioning
confidence: 99%
“…Stressors often cause dynamic changes in the hormones in the hypothalamic-pituitary-adrenal (HPA) axis ( Khilji et al, 2018 ). The activation of the HPA axis in broilers under heat stress conditions leads to elevated plasma glucocorticoid corticosterone ( Quinteiro-Filho et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BHA on some hematological characteristics can also be attributed to thyroid hormones. These hormones play an essential role in the progress of lymphoid organs and the arranging of immune assignment in birds and raise the number of lymphocytes, phagocytes, IgM, and IgG (14), as indicated by Keshavarz et al (15) to giving thyroxine at a concentration of 0.3 mg/bird daily to laying hens at the age of 47 weeks for 14 weeks led to an increase in the number of white and red cells, and this was identical to the results of this study. The increase in hemoglobin and packed cell volume is due to a direct relationship with an upraise in the number of RBC.…”
Section: Discussionmentioning
confidence: 99%